THE RELATIONSHIP OF VISUAL PERCEPTION OF HEALTH IMAGES ON CIGARETTE PACKAGING WITH ADOLESCENT SMOKING BEHAVIOR - Wiana, Rama Dwissa; Permana, Dwika Lutfhi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
Smoking is one of the problems experienced by adolescents. Anytime and anywhere we often encounter teenagers who smoke. The purpose of the study was to analyze the relationship between the visual perception of health images on cigarette packaging with adolescent smoking behavior at SMK Dwija Bhakti 1 Jombang Class X Computer and Network Engineering Expertise Program. Design survey analytical research with a cross sectional approach. The population in this study was all students of SMK Dwija Bhakti 1 Jombang class X computer and tissue engineering expertise program who smoked with a total of 34 students and a total sample of 31 students taken using simple random sampling techniques. Independent variables of visual perception and dependent variables of adolescent smoking behavior. Data collection with the dissemination of questionnaires, data processing editing, coding, scoring and tabulating, data analysis with statistical tests of spearman rank. The results showed that of the 31 respondents, most of them had a negative perception of 18 students (58.1%) and most of the respondents had mild smoking behavior as many as 21 students (67.7%). The value of p = 0.03 < ? 0.05 which means H1 is accepted. The conclusion in this study is that there is a relationship between the visual perception of health images on cigarette packaging and adolescent smoking behavior